Soft skill elements in structured clinical nursing assessment for undergraduate nursing student: a systematic review - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin; Chong, Mei Chan (2019)
Introduction: Acquiring soft skill competencies becomes increasingly important and relevant for nursing graduates. It is crucial to have holistic graduate nurses who equip with clinical skill and soft skill in current healthcare delivery system. Objective: The aim of this systematic review was to appraise and synthesize the available evidence that examines the soft skill elements in clinical nursing assessment for undergraduate nursing students. Methods/Materials: The systematic review was in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Published quantitative and qualitative studies that examined the soft skill elements in nursing clinical skill assessment and clinical nursing practice were retrieved. Relevant studies were identified using combined approaches of electronic database such as Science direct, Sage Publication, CINAHL, Springer link, PubMed, Proquest, Ovid, and Clinicalkey for Nursing search with language filters but were limited to articles published from January 2000 to March 2019, handsearching journals and visually scanning references from retrieved studies. Two reviewers independently conducted the quality assessment, data extraction, and analysis on all included studies. Result: This review screened 2708 articles including abstracts and full-text records, resulting in 17 included studies. Ten quantitative studies and 7 qualitative studies were identified for this evaluation. Many researchers have discussed the specific soft skills needed for nursing graduates to be successful. Without developing adequate soft skill elements in the clinical skill assessment, students are graduating unprepared to be successful in the workplace. Overall finding from the 17 studies described that there is still less pay attention on soft skill assessment in structured clinical skill assessment in undergraduate nursing students. Conclusion: Hence, soft skill competencies in clinical assessment of nursing students is a crucial issue for nursing academics. There is a need to consider and adopt soft skills in clinical skill assessment as in nursing education to improve the quality of nursing graduates and ultimately to create a positive impact on patient outcomes.